New perspectives in service-learning : research to advance the field - Welch, Marshall; Billig, Shelley (Advances in service-learning research., 2004)
This installment in the book series "Advances in Service-Learning Research", edited by Shelley H. Billig and Marshall Welch, focuses on New Perspectives in Service-Learning.